Optimization of copper top-side metallization for high performance SiC-devices - Behrens, Tim; Suenner, T.; Geinitz, Eckart; Schletz, Andreas; Frey, Lothar (2013)
While aluminum-based metallization schemes on Si have been optimized for the last decades, only few investigations have been done on copper metallization with SiC-devices. Thus, in this work the mechanical as well as the electrical interactions of this metallization system have been analyzed and optimized for SiC-devices in high reliability applications. For optimizing the adhesion of the copper metallization stack on SiC devices, different metallization schemes consisting of adhesion promoters (Ti, Cr, Al, Ta, WTi), diffusion barriers (TiN, Ta, WTi), and the final copper layer have been tested by peel-tests. For investigating the electrical interactions TLM measurements as well as leakage-current measurements have been done on copper metalized SiC samples. © (2013) Trans Tech Publications, Switzerland.
Keywords: Adhesion; Copper metallization; Electronic packaging; Peel test; SiC ohmic contact; Silicon carbide; Thick wire bonding